1995
DOI: 10.1523/jneurosci.15-05-04013.1995
|View full text |Cite
|
Sign up to set email alerts
|

Long aboral projections of Dogiel type II, AH neurons within the myenteric plexus of the guinea pig small intestine

Abstract: Enteric AH neurons, with multipolar Dogiel type II morphology, project around the circumference of the intestine to myenteric ganglia, the submucosa and mucosa. Using retrograde labeling in vitro, intracellular recording, dye filling and immunohistochemistry, the projections of these neurons along the intestine were studied. When the retrograde tracer, Dil, was applied to the myenteric plexus, labeled nerve cell bodies were located up to 111 mm orally but only 13 mm aborally, demonstrating a marked difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
2
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 31 publications
6
70
2
3
Order By: Relevance
“…The functional projections were asymmetrical, with long descending projections but no, or very short, ascending projections. Similar projections have been found for distension-sensitive Dogiel type II neurons (9) in the guinea pig ileum. Furthermore, the projections of extrinsic nerves would be predicted to be symmetrical, with equal lengths in the oral and anal direction, which suggests that the asymmetrical sensory pathways seen here are of intrinsic origin (i.e., an enteric neuron).…”
Section: Projection Lengths Of Neurons Within the Reflex Pathwayssupporting
confidence: 81%
“…The functional projections were asymmetrical, with long descending projections but no, or very short, ascending projections. Similar projections have been found for distension-sensitive Dogiel type II neurons (9) in the guinea pig ileum. Furthermore, the projections of extrinsic nerves would be predicted to be symmetrical, with equal lengths in the oral and anal direction, which suggests that the asymmetrical sensory pathways seen here are of intrinsic origin (i.e., an enteric neuron).…”
Section: Projection Lengths Of Neurons Within the Reflex Pathwayssupporting
confidence: 81%
“…In the guinea pig, Brookes et al, (1991Brookes et al, ( , 1995 identified Calr-IR in "small" Dogiel type I neurons of both the myenteric and the submucosal plexus. However, our results and those of Mann et al (1997) indicated that in the rat, Calr-IRN are entirely Dogiel type II.…”
Section: Discussionmentioning
confidence: 99%
“…Second, while electrical stimulation evokes fast EPSPs mediated by nAChR in all S/uniaxonal neurons of the descending inhibitory pathway, many of these neurons also exhibit fast EPSPs mediated by either P2X or 5-HT 3 receptors [56,67,142]. Third, some sensory neurons have long anally projecting axons as well as circumferentially projecting axons [18], which complicates interpretation of data arising from pharmacological studies designed to isolate specific classes of synapses.…”
Section: Circuits Regulating Motility Reflexesmentioning
confidence: 99%